Gestational diabetes mellitus. Unresolved issues and future research directions. - Okun, N. (College of Family Physicians of Canada, 1997)
OBJECTIVE: To summarize the controversial aspects of gestational diabetes (GDM) and introduce readers to possible relevant research questions that could be examined to provide clinicians with good-quality data on which to base decisions about this relatively common pregnancy-related issue. DATA SOURCES AND STUDY SELECTION: Ongoing review of the English literature related to GDM. Sources were not restricted to prospective, controlled trials, as these are severely limited in number. SYNTHESIS: Controversial issues include the relevance of GDM to clinically meaningful outcomes in the index pregnancy, the effectiveness of current therapy in altering these outcomes, and the resultant questionable relevance of routine screening and diagnosis of an entity with as yet uncertain significance in pregnancy. CONCLUSIONS: Suggested questions to be addressed in multicentre controlled trials include randomization with respect to screening and with respect to treatment. Until such trials are completed, continuing with a standard approach to screening, diagnosis, and treatment, such as that suggested by the third international workshop on GDM, is recommended.